1992
DOI: 10.1007/bf00201805
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal convergence (STC) in otolith neurons

Abstract: It has been recently demonstrated that some primary otolith afferents and most otolith-related vestibular nuclei neurons encode two spatial dimensions that can be described by two vectors in temporal and spatial quadrature. These cells are called broadly-tuned neurons. They are characterized by a non-zero tuning ratio which is defined as the ratio of the minimum over the maximum sensitivity of the neuron. Broadly-tuned neurons exhibit response gains that do not vary according to the cosine of the angle between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
40
0
1

Year Published

1992
1992
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 24 publications
6
40
0
1
Order By: Relevance
“…Under the assumption that converging inputs to a neuron add linearly, it has been proposed (Baker et al 1984a) and theoretically demonstrated (Angelaki 1991b) that "non-cosine-like" tuning characteristics can arise from inputs which exhibit "cosine-like" spatial properties only if the inputs differ in both their temporal and spatial properties. An interesting question is whether the otolith afferents show "non-cosine-like" spatial properties.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Under the assumption that converging inputs to a neuron add linearly, it has been proposed (Baker et al 1984a) and theoretically demonstrated (Angelaki 1991b) that "non-cosine-like" tuning characteristics can arise from inputs which exhibit "cosine-like" spatial properties only if the inputs differ in both their temporal and spatial properties. An interesting question is whether the otolith afferents show "non-cosine-like" spatial properties.…”
Section: Discussionmentioning
confidence: 98%
“…It has been shown that some otolith afferents innervating the peripheral extrastriola may branch and innervate several hair cells within a terminal field diameter of approximately 100 ~t (Fernandez et al 1990). The non-zero sensitivity of primary otolith afterents in "null" orientations, whenever present, could be created by different temporal characteristics of inputs from hair cells which have somewhat different polarization vectors and are innervated by a single afferent fiber (Angelaki 1991b).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that simple convergence between regular and irregular otolith afferents with different polarization vectors result in "two-dimensional" neurons with one vector encoding linear acceleration and the other responding to the derivative of linear acceleration (jerk; Angelaki 1992c). It should be added that the response vectors $1 and $2 do not necessarily represent the converging otolith afferent vectors (Angelaki 1992a). Generally, STC between any number of otolith afferents having polarization vectors with different orientations (not necesarily orthogonal) can create "two-dimensional" neurons.…”
Section: Two-dimensional Spatio-temporal Linear Accelerometersmentioning
confidence: 99%
“…The advantages of 3D over 2D translational experiments have been previously demonstrated (Chen-Huang and Peterson 2006). As predicted by geometry, the tuning ratio, a measurement of spatiotemporal tuning properties (Angelaki 1992;Schor and Angelaki 1992), derived from 2D-only data sets might overestimate or underestimate the 3D ratio. Further, the likelihood of classifying simple (cosine-tuned) neurons as complex (STC) type increases if data, small in modulation and large in noise, are available only from a nonpreferred plane (Chen-Huang and Peterson 2006).…”
Section: Introductionmentioning
confidence: 98%
“…In other words, the sensitivity of translation-related responses becomes broadly tuned, whereas the phase changes gradually with stimulus direction. This complex tuning response has been successfully modeled as resulting from the summation of translation-related inputs that are in spatial and temporal quadrature (Angelaki 1992) or spatiotemporal convergence (STC).…”
Section: Introductionmentioning
confidence: 99%